Simultaneous bilateral chronic volar lunate dislocation: A case report - Ishizaki, A.; Omokawa, S.; Hasegawa, H.; Nagashima, M.; Shimizu, T.; Kawamura, K.; Tanaka, Y. (JBJS Case Connector, 2021)
Case: A 24-year-old professional judo competitor suffered injuries to both the wrists when he fell on his back while lifting a 90-kg barbell in the bilateral dorsiflexed wrist position. Simultaneous bilateral volar lunate dislocation had been missed for a year. The degenerated lunates were simultaneously removed using a palmar approach. At 12 months postoperatively, the patient returned to judo competitions without pain. Radiography showed no progression of the intercarpal alignment abnormality. Conclusion: Simultaneous bilateral chronic volar lunate dislocation is extremely rare. Long-term follow-up is necessary to check for carpal alignment.